Booking parking apps / Ariff Hakimi Ahmad Khusairi … [et al.] - Ahmad Khusairi, Ariff Hakimi; Abd Jalil, Akmal Ikhwan; Abdul Rahman, Muhammad Khairul Aiman; Mohd Fauzi, Muhammad Zulhilmi; Rafie, Muhammad Ilmam (2022)
Planning a business may have looked like a piece of cake, but the truth is, only those who bear it know the struggle. Planning requires a lot of patience, to prepare one's self before embarking on a hectic world of entrepreneurship. Our partnership, EZ Parking has done thorough research and planned our journey systematically. It is to ensure that we will be fully prepared should there be any hindrance that might slow down our business. This business plan is a comprehensive explanation of the operation and marketing strategies, budgeting as well as expenses that will occur throughout the entire operation. We have narrowed the scope of our starter targeted area, of which AEON Bandaraya Melaka. An application known as EZ Parking will help the shoppers, shopping mall's employee and anyone who are interested to park their car in the shopping complex. This apps make it easier for parking enforcement to electronically monitor parking spaces. This apps can also increase in safety in the shopping mall. Drivers are less distracted searching about for a place since they know where they can park their automobile. They will have their complete concentration on the road. By keeping their attention on the road, accidents will reduce and safety will enhance for themselves, other cars and pedestrians. To conclude, the ultimate goal of EZ Parking is not only focusing on numbers of profits, but to help shopping malls in Malaysia to avoid heavy traffic and simultaneously smooth one’s shopping experience.